Innovative Approaches to Talent Development in Optoelectronic Information Science and Engineering under the Emerging Engineering Perspective (Contemporary Education and Teaching Research, 2025)
In the context of the accelerated evolution of scientific and technological revolutions and industrial transformations, the development of emerging engineering education has become a key direction for reforms in higher engineering education. As a frontier discipline, Optoelectronic Information Science and Engineering has been widely applied in fields such as communications, healthcare, and energy. However, traditional training models can no longer meet the innovation-driven and practice-oriented talent requirements of emerging engineering. Thus, exploring innovative pathways for talent cultivation in this discipline has become imperative. Focusing on this issue, the present study examines innovative approaches to talent cultivation in the field. It analyzes the new requirements posed by emerging engineering education, and proposes pathways such as curriculum system optimization, enhanced practical teaching, and strengthened faculty development. The aim is to offer references for cultivating high-quality talents in Optoelectronic Information Science and Engineering who can meet the needs of emerging engineering, thereby promoting the sustainable development of the discipline and responding to the urgent societal demand for qualified professionals.